Satisfaction with social support in the elderly of the district of Bragança - Grande, Carla Maria Perdigão Martins (2016)
This is a demographic transition scenario with implications in all areas of social life: it is unacceptable to face aging without reflecting on the problems around opportunities for older people, including satisfaction with social support. Social support is particularly important to facilitate an independent and fulfilling life in the community for the elderly. Objectives: To assess the satisfaction of elderly people with social support (individuals aged over 65 years) living in the district of Bragança, by applying a sociodemographic questionnaire and the Satisfaction Scale with Social Support (ESSS) of Ribeiro (2011) [1]. Starting from the elderly population living in Bragança district, we developed an observational, analytical and cross-sectional study with a quantitative approach, with a sample of 517 subjects, mostly females (54.9 %; n = 284); aged between 65 and 74 years old (45.3 %; n = 234); married or living in consensual union (61.9 %; n = 320); residents in rural areas (69.8 %; n = 361); with sons and daughters (89.0 %; n = 460); and illiterate (50.7 %; n = 262). The sample under study has average social support, which allows us to infer that the elderly is, in general, satisfied with the social support which they have, and the support received from friends is that which gives them more satisfaction, expressing less satisfaction with family support. It is observed that most of the variables are, in the case of the elderly, determinants of their satisfaction with social support.